The Association of Emergency Severity Index Score and Patient and Family Experience in a Pediatric Emergency Department - Adam A Vukovic MD, MEd; Callie Krentz MD; Abigail Gauthier MD; Nusrat Harun PhD; Stephen C Porter MD, MSc (Journal of Patient Experience, 2023)
The study aim was to determine the relationship between a patient's Emergency Severity Index (ESI) score and their or their family's response to the key performance indicator (KPI) question on the post-visit patient and family experience (PFE) survey. Retrospective review of patients presenting to the Pediatric Emergency Department between July 1, 2021, and June 30, 2022, who completed the KPI question on an associated post-visit survey. We performed univariate analyses on all candidate variables; multivariable linear regression identified independent predictors of KPI on the PFE survey. A total of 8136 patients were included in the study. Although ESI score was significantly associated with PFE in univariate analysis, this association was lost in the multivariable model. Independent associations were appreciated with race/ethnicity, time to provider, length of stay, and procedure performance during the visit. Although ESI is not independently associated with PFE in this study, its interaction with factors such as time to provider, length of stay, and procedure performance may be important for emergency department providers creating interventions to impact experience during low acuity visits.